National Integration Slogans in Printed Mass Media in the Era of New Order Regime in Indonesia, 1968-1998 - Alkatiri, Zeffry; Albar, Muhammad Wasith (TAWARIKH, 2010)
ABSTRACT: This article is a research finding aiming at reconstructing and analyzing the slogans related to Indonesian nation integration in the 1968-1998 New Order regime printed mass media. The research questions of this paper are as follows: (1) What slogans were used?; and (2) How and why did the national integration propaganda slogans take place in the New Order regime? The article also searched for how the New Order regimeâs machine produced a lot of slogans regarding the ideas of national integration done in various ways. This paper used discourse analysis and historical interpretation. The reason why this research was conducted is the fact that the slogans on the national integration in the New Order regime have not yet documented and analysed. This analysis deals with the understanding of slogan texts as the record of the New Order regime. Another objective of the research is to complete the study on New Order regime, as well as as a comparative study with the slogans taking place in the Reform era. KEY WORDS: Slogan, New Order regime, printed media, national integration, and comparative study.Â Â Â About the Authors: Dr. Zeffry Alkatiri and Muhammad Wasith Albar, M.Hum. are Lecturers at the Department of History, Faculty of Humanities UI (University of Indonesia), Campus UI Depok 16424, West Java, Indonesia. They can be reached at: zeffry_al@yahoo.com and muhammadwasithalbar@yahoo.comHow to cite this article? Alkatiri, Zeffry & Muhammad Wasith Albar. (2010). âNational Integration Slogans in Printed Mass Media in the Era of New Order Regime in Indonesia, 1968-1998â in TAWARIKH: International Journal for Historical Studies, Vol.2(1) October, pp.109-122. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (August 12, 2010); Revised (September 24, 2010); and Published (October 28, 2010).